IMPLEMENTASI PROGRAM BANTUAN OPERSIONAL SEKOLAH (BOS) SMA NEGERI 1 BAMBALAMOTU KABUPATEN MAMUJU UTARA - Jayadi, Hendra (Katalogis, 2018)
The purposes to be achieved were to determine and to analyze the implementation of School Operational Assistance Fund Program at State Senior High School 1 of Bambalamotu in North Mamuju Regency. The type of this study was qualitative study by taking people, employees of State Senior High School 1 of Bambalamotu, staff of North Mamuju Department of Education, Culture, Youth, and Sportsas informants puposively. The data collection technique comprised participant observation, in depth interview, documentation, and triangulation.The data analysis technique comprised data reduction, data display, conclusion, and verification.The results showed that the implementation of School Operational Assistance Fund Program at State Senior High School 1 of Bambalamotu in North Mamuju Regency had been running, but not yet optimal due to the content of policywhere determination of poor studentscriteria was not accurate in the School Budget Plan, resulting in many less fortunate students who did not get any help from School Operational Assistance Fund. The resources involved were limited, both in terms of quality and quantity, resulting in still less skilled program managers and lack of monitoring functions. Whereas the implementation context was not maximized due to the low level of implementers’ compliance,making School Operational Assistance Fund Program has not been on target in accordance with designation and school needs.